2022
DOI: 10.3389/fped.2022.940294
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes of Cornelia de Lange syndrome caused by non-cohesion genes: Novel variants and literature review

Abstract: BackgroundCornelia de Lange syndrome (CdLS) is a genetic disorder caused by variants in cohesion genes including NIPBL, SMC1A, SMC3, RAD21, and HDAC8. According to the 2018 consensus statement, a patient with clinical scored ≥ 11 points could be diagnosed as CdLS. However, some variants in non-cohesion genes rather than cohesion genes can manifest as phenotypes of CdLS.ObjectivesThis study describes six variants of non-cohesion genes (KDM6A, KMT2D, KMT2A ANKRD11, and UBE2A), and assesses the reliability of 11-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Alternatively, BRD4 may have unique enhancer regulatory roles independent of NIPBL and cohesin during craniofacial development. Aside from cohesin subunits and BRD4, several enhancer regulatory factors can also be mutated in CdLS including the EP300 histone acetylase (Cucco et al 2020;Woods et al 2014), MED13L of the mediator complex (Aoi et al 2019), as well as KDM6A and KMT2D histone modifiers (Shangguan and Chen 2022) that function at enhancers and regulate cNCC osteoblast differentiation (Shpargel et al , 2020Wang et al 2016;Shpargel and Quickstad 2023).…”
Section: Development • Accepted Manuscriptmentioning
confidence: 99%
“…Alternatively, BRD4 may have unique enhancer regulatory roles independent of NIPBL and cohesin during craniofacial development. Aside from cohesin subunits and BRD4, several enhancer regulatory factors can also be mutated in CdLS including the EP300 histone acetylase (Cucco et al 2020;Woods et al 2014), MED13L of the mediator complex (Aoi et al 2019), as well as KDM6A and KMT2D histone modifiers (Shangguan and Chen 2022) that function at enhancers and regulate cNCC osteoblast differentiation (Shpargel et al , 2020Wang et al 2016;Shpargel and Quickstad 2023).…”
Section: Development • Accepted Manuscriptmentioning
confidence: 99%
“…BRD4 and ANKRD11 have recently been added to a list of genes causing CdLS [51]. BRD4 encodes chromatin-associated proteins which cooperate with NIPBL in transcriptional regulation.…”
Section: Cohesin Complexmentioning
confidence: 99%
“…Constipation and GERD are more common in patients with variants in the NIPBL and SMC1A genes, visual impairment in NIPBL, SMC1A, and HDAC8, structural brain abnormalities in NIPBL, and sleep problems in NIPBL and SMC1A [56,66]. Dysmorphic features that meet the clinical diagnostic criteria for CdLS can also be seen in people with changes in the BRD4, RAD21, or ANKRD11 genes, although they are not as severe or common [7,51]. Comprehensive molecular analysis in a cohort of 716 probands with CdLS revealed that causative variants in genes such as AFF4, ANKRD11, ARCN1, ARID1B, ASXL2, and others account for a significant proportion of etiologies beyond the traditional CdLS genes (25% of probands) [7].…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%